Strategi Strategi Kampanye Politik Faisal, SE dalam Pemilu Legislatif Kota Bekasi Tahun 2024 - Anastasya Putri Andini; Rachmat Ramdani; Gun Gun Gumilar (LPPM Universitas Abdurrab, 2026)
The increasingly tight political competition in the 2024 Bekasi City Legislative Election, particularly with the electoral district (Dapil) shift experienced by Faisal, SE., necessitated an effective campaign strategy. This study aims to analyze Faisal's political campaign strategy based on the political marketing mix theory (4P) by Niffenegger (1989). A qualitative approach with a case study design was employed, utilizing interviews, observations, and documentation for data collection. The results indicate that Faisal successfully built an image as a young politician close to the people through campaign products based on a track record of social services, specifically in education and health. The political price offered was non-transactional, focusing instead on the sacrifice of time, energy, and moral commitment. Strategy placement focused on the support base in Pondok Gede, with information distribution expanded through digital media. Promotion was carried out through integrated face-to-face activities, social media, and campaign props. This research contributes to political marketing theory by demonstrating that non-material sacrifice (psychological price) and social track records (tangible products) are more effective in building voter loyalty in a new district than transactional approaches